Peran Guru dalam Pendidikan Karakter Anak di TK Aisyiyah Bustanul Athfal 1 Kemranjen - Zaidah, Vina Misykah; Tatik Ariyati (Institut Agama Islam Negeri Madura, 2024)
This study examines the importance of character education for early childhood at TK Aisyiyah Bustanul Athfal 1 Kemranjen, aiming to analyze the role of teachers in character development. The research employs a qualitative approach with a case study design, involving non-participant observation, unstructured interviews, and documentation. The findings indicate that character education plays a crucial role in shaping positive behavior and social skills in children. Teachers implement various strategies, such as habituation, modeling, appreciation, and contextual learning, to instill character values. Collaboration between teachers and parents, along with the creation of a conducive learning environment, are also vital factors in character development. This study underscores that consistent and integrated character education can build a strong foundation for children's personality development in the future.